ACCOUNTING CASES. (The Accounting Review, 1940)
The statements of the Homestake Mining Co., a gold-mining company, and of its wholly owned subsidiaries, the Golden Gate Mine and Timber Company and the Wyodak Coal and Manufacturing Company, provide an interesting example of the treatment of depletion and of the difference between percentage depletion allowed by the Federal income tax law and unit depletion based upon the cost or March 1, 1913 values of the property. The Bureau of Internal Revenue for income tax purposes at $13,250,416.16 established the March 1, 1913 value of the ore body of the Homestake Mining Co. For a number of years depletion based on a percentage of gross income as permitted by the Federal income tax law was credited partly to depletion reserve on cost or market values as of March 1, 1913 "on a per-unit basis, and the remainder to "Depletion reserve, percentage basis in excess of cost or March 1, 1913 value." A change in the treatment of investments in subsidiaries by the parent company, required by the United States Securities and Exchange Commission, is also of significance.